A people's history of Detroit - Jay, Mark (Duke University Press, 2020)
"A PEOPLE'S HISTORY OF DETROIT provides a sweeping, Marxist account of Detroit's development and dispossession over the past century. Throughout the book, Mark Jay and Philip Conklin show how the revitalization as well as demise of Detroit are part and parcel of the logic of capitalism. Building on other recent works that show how precarity, uneven development, and colossal waste are constitutive parts of capital's relentless pursuit of surplus value, the book offers a powerful antidote to recurrent narratives of market triumphalism. Chapter 1 analyzes contemporary Detroit, arguing that increasing investment downtown and the dispossession of neighborhoods are not separate entities, but a result of the same process of unequal development. The second chapter looks back at Detroit's birth as a global industrial center and how increased demands for labor led to ethnic divisions among workers and, later, heightened racial violence. Chapters 3 and 4 explore the radical movements and politicized organizations that came out of the 1960s. The Black Panther Party is one of these groups, which called for a restructuring of the political economy but were met with severe repression. The final chapter further discusses the "dialectic of repression and integration" these groups faced as well as the victories of state forces allied with corporations. Among the issues that emerged at this time were the growing unemployment rates and the lack of willingness on behalf of the state to accept crime as a result of social dislocation. This book will be of interest to students and scholars in sociology, urban studies, and African American studies"--